Analysis of Radio Model Performance for Clustering Sensor Networks - Bello-Salau, H; Salami, A. F.; Anwar, Farhat; Islam, Md. Rafiqul (International Frequency Sensor Association (IFSA)., 2011)
Contemporary advancements in the field of wireless technology and sensor instrumentation have led to the proliferation of novel protocols which are specially designed for low-power networks such as wireless sensor networks. In the field of wireless sensor networks, researchers are currently interested in tackling the challenge of designing an optimum routing protocol that will satisfy the application and network requirements with minimum consumption of energy. Cluster-based routing protocols have been found to be more advantageous to other types of routing techniques when there is a relatively huge number of a sensor node to be deployed. This paper is an investigation of the performance of selected cluster-based routing protocols with special emphasis on the effectiveness of their radio propagation models.